On the Gauss Map of Surfaces of Revolution with Nonlightlike Axis in Minkowski 3-Space - Minghao Jin; Donghe Pei (Abstract and Applied Analysis)
We study surfaces of revolution with a nonlightlike axis in 3-dimensional Minkowski space and classify such surfaces in terms of the Gauss map G that satisfies the condition ΔhG=ΛG, with Λ being a 3×3 real matrix. Furthermore, this paper completes the classification problem of surfaces of revolution in Minkowski 3-space given by Jin et al. (2013).